Toxic workplace, workstress, and employee performance: Predictive model - Prasetyo, Eko Agus; Maghfirah, Ayya; Ridho, Ali; Nuqul, Fathul Lubabin; Muallifah, Muallifah; Rahayu, Iin Tri (Journal of Indonesian Psychological Science (JIPS), 2025)
An unhealthy work environment and work stress can have a major impact on employee performance productivity. The purpose of this study was to predict employee performance based on toxic workplace and work stress at the Central Java DIY Contact Center company. The determination of a sample size of 150 participants was carried out by Convenience Sampling. The application of multiple linear regression showed results where toxic workplace and work stress contributed negatively. The results of this study are that toxic workplace and work stress have a negative and significant effect on employee performance at Central Java DIY Contact Center company. Productive employee performance can grow from comfortable work environment conditions, employees who do not experience work stress at work. The results of this study are expected to provide benefits for Central Java DIY Contact Center employees and can be useful for companies in creating a comfortable work environment, minimal work stress in increasing employee performance productivity at the Central Java DIY Contact Center company.